LEGAL ANALYSIS OF THE TWO-TRACK SENTENCING SYSTEM FOR CHILDREN COMMITTED AGGRAVATED THEFT IN THE JUVENILE CRIMINAL JUSTICE PROCESS (STUDY OF DECISION NUMBER 1/PID.SUS-ANAK/2025/PN SGL) - Agusto Imanuel; Muhamad Adystia Sunggara; Enny Agustina (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Children are a national asset whose existence is crucial to ensuring the survival of a nation. Therefore, to support this goal, the future of children and their livelihood security must be considered from all aspects, from economics to education to health, and most importantly, legal protection. Legal protection is paramount because today many children are involved in criminal acts, resulting in their status changing to children in conflict with the law, and many are sentenced to prison in Child Development Institutions. This has the potential to threaten the continuity of children's access to educational rights. It must be understood that fostering in a foster institution does not necessarily break the chain of recurrence of criminal acts by children, and placement of children in foster institutions also has the potential to increase the state's financial burden and may lead to overcapacity in society. Therefore, Indonesia is slowly trying to implement a double-track criminal justice system to accommodate the interests of children in conflict with the law so that their rights are still fulfilled. As an analysis of this system, the author attempted to conduct research on the Sungailiat District Court Decision Number 1/Pid.Sus-Anak/2025/PN Pgp. Using a normative legal research method, the author attempts to examine the application of two criminal justice systems in handling juvenile cases. Through a literature review of the collected legal materials, the author found that implementing two criminal justice systems in handling juvenile cases is not easy. Many factors must be ensured for the success of these two criminal justice systems.The child's age as a tool to identify children who may be subject to imprisonment or other criminal penalties, analysis of the community guidance research report, criminal threats against children, a description of the public prosecutor's demands outlining sanctions for the action, the availability of supporting facilities and the budget for implementing the action against the child. Each component supports each other, and if one component is not met, the two-track criminalization formulation cannot be implemented. And this occurs in case handling.Sungailiat District Court Decision Number 1/Pid.Sus-Anak/2025/PN Pgp which ultimately cannot apply the decision to take action against the child even though the conditions for the child to be subject to action have been fulfilled in terms of the actions and the threat of punishment imposed on the child.